Positive personality traits and their impact on positive organizational behavior in the work environment A field study on the staff of some faculties of Alasmarya Islamic University - Agob, Ayada Masoad; Lahderi, Rabia Omar (Journal of Educational and Psychological Sciences, 2023)
Increasing interest at the present time in studying the characteristics of the positive personality, including the inherent features that make the individual a high degree of self-efficacy, and the consequent feeling of the individual’s reassurance, satisfaction and success in his social and professional life. Positive self-image, self-commitment, orientation towards others, cultural autism) and its reflection on positive organizational behavior and its dimensions (performance, job satisfaction, organizational commitment), as well as knowing the impact of some demographic variables of employees on positive personality traits on the one hand, and positive organizational behavior on the other. Another such as (gender, age, educational qualification, years of experience, job position). To achieve this purpose, the two researchers chose a sample of (89) employees working at Al Asmarya University. They also used the positive personality traits scale, the positive organizational behavior scale, and used the descriptive relational approach as it is the appropriate approach to achieve the objectives of this research. The results concluded that the level of positive personality traits (positive self-image, self-discipline, life orientation, and cultural orientation) among the sample of employees was high on the total score of the scale, and that the level of organizational behavior among the sample of employees was generally satisfactory, as evidenced by the ratio The percentage of the total score of the scale amounting to (58.79%), and the level of job performance specifically reached (82%), which is a high percentage, and that there is a statistically significant correlation at the level of significance (0.01) between each of the positive personality traits and organizational behavior among the sample members, and there are no differences Statistically significant on the two measures of positive personality traits and organizational commitment according to the variables (age - education - experience). The two researchers recommended providing training programs and workshops for employees working in colleges to develop organizational behavior, spread a culture of organizational behavior, and enlighten them about its importance in professional life. Providing training counseling programs targeting employees in the university’s faculties to develop their positive psychological skills to enhance their ability to deal with various situations and conditions in the field of work. And the intensification of self-development and engineering programs targeting employees and administrators within the university and the development of deficiencies in the aspects of personality revealed by the research results.